LEGAL BASIS OF SETTLEMENT OF CREDIT OPERATIONS IN THE ENTERPRISES - Mo‘ydinov Ozodbek Olimjonovich (European Science Publishing, 2026)
The strict adherence of these banks to the principles of loan repayment, processing, solvency and security, as stipulated in current legislation and agreed upon with the parties, is studied. Depending on the term, bank loans are short and long-term. With the temporary term (date) of the loan. The legal and regulatory documents on the procedure for repaying loans are studied.
Keywords: Bank, credit, Commercial bank, balance sheet, liquidity, Business entities, liabilities.